Perceived Community Environmental Factors and Risk of Five‐Year Participation Restriction Among Older Adults With or at Risk of Knee Osteoarthritis. Issue 7 (2nd June 2017) - Vaughan, Molly W.; Felson, David T.; LaValley, Michael P.; Orsmond, Gael I.; Niu, Jingbo; Lewis, Cora E.; Segal, Neil A.; Nevitt, Michael C.; Keysor, Julie J.
Abstract : Objective: Older adults with knee osteoarthritis (OA) who live in environments with mobility barriers may be at greater risk of developing participation restrictions, defined as difficulties in engagement in life situations. We investigated the risk of participation restriction over 5 years due to self‐reported environmental features among older adults with knee OA. Methods: Participants from the Multicenter Osteoarthritis (MOST) Study self‐reported participation at baseline, 30 months, and 60 months using the instrumental role subscale of the Late Life Disability Index (LLDI). Data on self‐reported environmental features were from the Home and Community Environment questionnaire administered in the MOST Knee Pain and Disability study, an ancillary study of MOST. The relative risks (RRs) of developing participation restriction at 60 months, indicated by an LLDI score <67.6 out of a possible 100, due to reported high community mobility barriers and high transportation facilitators, were calculated using robust Poisson regression, adjusting for covariates. Results: Sixty‐nine of the 322 participants (27%) developed participation restriction by 60 months. Participants reporting high community mobility barriers at baseline had 1.8 times the risk (95% confidence interval [95% CI] 1.2–2.7) of participation restriction at 60 months, after adjusting for covariates. Self‐report of high transportation facilitators at baseline resulted in a reduced but statistically nonsignificant risk of participation restriction at 60 months (RR 0.7, 95% CI 0.4–1.1). Conclusion: Higher perceived environmental barriers impact the risk of long‐term participation restriction among older adults with or at risk of knee OA. Approaches aimed at reducing the development of participation restrictions in this population should consider decreasing environmental barriers.